Case report and literature review: Isolated HCC- recurrence in gallbladder after curative resection - Zhang, Shi-Ran; Ma, Yu; Zhou, Bo; Li, Guang-Yao; Chen, Ping; Chen, Geng (Frontiers in Surgery, 2023)
Background Liver resection (LR) is considered the mainstay treatment for eligible patients with hepatocellular carcinoma (HCC) and provides a 5-year overall survival (OS) of 60%–80%. However, the recurrence rate within five years after LR remains high, ranging from 40% to 70%. Recurrence in gallbladder after liver resection is extremely rare. Here, we present a case of isolated recurrence in gallbladder after curative resection of HCC and review the relevant literature. No similar cases have been reported before. Case presentation A 55-year-old male patient was diagnosed with HCC in 2009 and subsequently underwent a right posterior sectionectomy of the liver. In 2015, the patient underwent liver tumor radiofrequency ablation and three transarterial chemoembolization (TACE) procedures in succession for HCC recurrence. In 2019, a gallbladder lesion was detected by computed tomography (CT) without perceivable intrahepatic focus. We performed an en bloc resection of the gallbladder and hepatic segment IVb. The pathological biopsy suggested that the gallbladder tumor was moderately differentiated HCC. The patient survived more than 3 years in good condition, and there were no signs of tumor recurrence. Conclusions In patients with isolated gallbladder metastasis, if the lesion can be resected en bloc without remnants, surgery should be the preferred option. Both postoperative molecularly targeted drugs and immunotherapy are expected to improve the long-term prognosis.